Analysing impacts of urban morphological variables and density on outdoor microclimate for tropical cities: A review and a framework proposal for future research directions - BANERJEE, Shreya (Institutional Knowledge at Singapore Management University, 2022)
Modifying urban morphology, defined as mass, density, and orientation of building stock in cities, are well-known heat mitigation strategies addressing urban heat islands (UHI) at various scales and consequent thermal discomfort. However, varying morphological aspects may have divergent effects on Outdoor Thermal Comfort (OTC) in cities. Unlike UHI, which is derived from urban-rural temperature differences, OTC can be quantified by thermal comfort indices considering the objective assessment of microclimatic variables including air temperature (Ta), relative humidity (RH), mean radiant temperature (TMRT), and wind speed (Va), as well as a subjective assessment of individual perception. In Singapore and other tropical cities, thermally uncomfortable conditions prevail year-round due to higher Ta and RH coupled with high solar irradiance from its equatorial location. To better understand the relationship between density related morphological variables, microclimate conditions and OTC in Singapore, we first conduct a systematic literature review to identify existing research gaps and uncertainties. We subsequently analyse prominent building bylaws and urban planning codes of Singapore to understand the potential comfort implications of existing urban morphological norms. Finally, we propose a methodological framework on how to address the gaps and uncertainties in mainstream urban design and urban planning process keeping into consideration microclimatic, comfort and socio-economic variables.